PENGARUH VARIABEL PERILAKU KARYAWAN AKUNTANSI TERHADAP KINERJA PERUSAHAAN (STUDI EMPIRIS PADA PERUSAHAAN BUMN DAN BUMD DI BANDA ACEH) - Mirna Indriani; Onny Loulyta (Jurnal Telaah dan Riset Akuntansi, 2008)
The purpose of this research is to analyze interpersonal relationship of accounting employee affecting to firm performance. The behavioral variables are conflict, shared value, balanced power, communication, confidence, and collaboration. For this purpose, structural equation modeling was used to test the research model’s relation. A questionnaire was distributed to 130 acoounting employees in 23 BUMN (Indonesian governments corporate) and 3  BUMD (local governments corporate).  We find that, although no significant relation between conflict and confidence, conflict and collaboration, shared value and confidence, shared value and collaboration, balanced power and confidence, confidence and collaboration, confidence and firm performance, there are significant relationship between balanced power and collaboration, communication and confidence, communication and collaboration, collaboration and firm performance. Keywords: Accounting department, departmental behavior, firm performance, Structural Equation Modeling (SEM)